'Darwin was Wrong.' The International Media Coverage of the Oreopithecus' Reinterpretation (1956–1959). (August 2016) - Florensa, Clara
Abstract: 'Darwin was wrong' was a headline that made news around the world in March 1956. Johannes Hürzeler, a Swiss palaeontologist, had just made public his theory that Oreopithecus bambolii, a fossil thus far classified as an extinct Old World monkey, was in fact a 12‐million‐year old hominid. That was 10 million years (!) older than the oldest hominids accepted at the time. Two years later he unearthed a complete skeleton of Oreopithecus in Italy. The echo of this discovery in the media was enormous yet the newspaper coverage in different western countries followed distinctive patterns. This paper will show these differences and point out possible explanations that go far beyond scientific disagreement. It will be argued that the press is a privileged source for comparing simultaneous reactions to the same scientific fact around the globe and for helping us discover national and supranational patterns of scientific discourse while linking them to their contexts. This paper also highlights the role of the news pieces as 'supports of knowledge.' Just like bones or scientific articles, news items circulate prompting in turn the circulation of other 'supports of knowledge' such as fossil remains or scientists.